Dakwah Kultural Pada Suku Gayo - Agung Pangeran Bungsu (Tsaqofah, 2021)
Cultural da'wah is the answer to the question of the da'wah model for the condition of a pluralistic Indonesian society. Da'wah that pays attention to the potential and ability of the target of da'wah produces much better output, of course. A preacher named Tengku Nasruddin developed a model of cultural da'wah in the Gayo community in the central part of Aceh. Tengku Nasruddin moves and innovates to develop the ability to understand the Al Quran until finally giving birth to students with brilliant achievements. This paper will try to review how the da'wah carried out by Tengku Nasruddin in the Gayo tribal community, the role of Tengku Nasruddin in the midst of society and the challenges of the da'i in developing the da'wah perspective of Tengku Nasruddin. This research method uses a descriptive qualitative approach to involve interpretation and a natural approach to the subject matter. It was found that the development of Tengku Nasruddin's cultural da'wah in the Gayo community emphasizes noble values by not coercing, and respecting the understanding of the target of da'wah until finally the message of goodness can be received.